Belonging and rural livelihoods: women`s access to land and non-permanent mobility at Merrivale farm, Mwenezi district, Zimbabwe - Mutopo, Patience (ERDKUNDE, 2014)
The fast track land reform programme in Zimbabwe has reshaped rural livelihoods as land has become a major asset for rural people. The major question that I sought to answer in this study is how have rural women become important actors in accessing land and shaping non-permanent mobile livelihoods in the context of the fast track land reform programme, riddled with conflicts? The data for the article is based on an ethnographic study that I undertook at Merrivale farm, Tavaka village, from April 2009 until August 2012. Major results that emanated are that women have become major actors in land acquisition and non-permanent mobile livelihoods. Problematising the notion of conflicts from two angles in this paper helps in understanding how mobility, linked to land acquisition and land use, is central in the evolving of conflicts in the new resettlements. Connecting land access, social networks and mobility to South Africa and the conflict paradigm brings out how land-based livelihoods are embedded with social mishaps in the new resettlement. The concept of “home” becomes central in resolving conflicts and affects how conflict mechanisms are reached at Merrivale or in South Africa. I explore the conflict resolution approaches women used to solve at Merrivale and in South Africa.